Network coding efficiency in the presence of an intermittent backhaul network - Achleitner, Stefan; La Porta, Thomas; Krishnamurthy, Srikanth V.; Quizhpi, Victor S. (IEEE International Conference on Communications (2003), 2016)
In infrastructure-lacking environments, like military areas of operation, the intermittent availability of backhaul networks leads to greater reliance on peer to peer data exchange. In such settings, mobile nodes use Delay Tolerant Network (DTN) protocols for exchanging location specific data. High transmission delay, packet loss and intermittent connectivity increases the need for efficient data transmission in such scenarios. In this paper, we evaluate network coding for efficient data exchange between mobile wireless nodes under the presence of an intermittent backhaul network, like a satellite or cellular link. We analyze the upper bound of savings achievable with network coding for single-hop packet transmission, and introduce a network coding algorithm focused on reducing the required number of packet transmissions in such a setting. Evaluation of our proposed data exchange protocol shows how network coding can be applied to reduce transmission delay and minimize the dependency on an intermittent backhaul network in a communication scenario typical of a military environment.